2020
DOI: 10.14202/vetworld.2020.1376-1387
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of virulent and resistant Escherichia coli strains to non-polar and polar compounds identified in Microplumeria anomala

Abstract: Background and Aim: Escherichia coli is one of the main pathogens responsible for veterinary and human infections, and it is associated with significant economic losses in the livestock, as it causes severe diseases to humans, particularly in children. For that reason, there is a need for introducing new drugs to treat E. coli diseases. The Brazilian species richness is a source of potential new antibacterial natural products. The study aimed at the biological and chemical investigation of the organic extract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…In recent decades, our researchers have been systematically developing projects aiming to identify antimicrobial active extracts from the Amazon and Atlantic Brazilian rainforests. We have studied more than 2,000 plant extracts and essential oils as antimicrobials against Staphylococcus aureus (Pinto, 2020), Staphylococcus epidermidis (Belo, 2022), Enterococcus faecalis (Castilho, 2009), Streptococcus mutans (Bento, 2020), Streptococcus sanguinis (Silva, 2009), Escherichia coli (Camargo, 2016), Pseudomonas aeruginosa, Candida albicans (Rudiger, 2021), Malassezia pachydermatis (Silva, 2018), Malassezia furfur ( Silva, 2018 ), and Listeria monocytogenes (Ceruso et al, 2020), which are shown in the present article as a result of a 15-year study in antimicrobial-active natural product identification (Suffredini et al, 2002;Suffredini et al, 2004;Suffredini et al, 2006a;Suffredini et al, 2006b;Younes et al, 2007;Castilho et al, 2013;Camargo and Suffredini, 2014;Castilho et al, 2014;da Silva et al, 2014;Costa et al, 2016;Suffredini et al, 2016;Martins et al, 2019a;Martins et al, 2019b;Camargo et al, 2020;Silva et al, 2020).. The present article reports a step-by-step methodology for identifying antimicrobial products in nature that comprises plant collection, the different tests used to analyze the in vitro antimicrobial activity, a test to determine toxicity, and a statistical-based algorithm to classify the extracts according to their potential.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…In recent decades, our researchers have been systematically developing projects aiming to identify antimicrobial active extracts from the Amazon and Atlantic Brazilian rainforests. We have studied more than 2,000 plant extracts and essential oils as antimicrobials against Staphylococcus aureus (Pinto, 2020), Staphylococcus epidermidis (Belo, 2022), Enterococcus faecalis (Castilho, 2009), Streptococcus mutans (Bento, 2020), Streptococcus sanguinis (Silva, 2009), Escherichia coli (Camargo, 2016), Pseudomonas aeruginosa, Candida albicans (Rudiger, 2021), Malassezia pachydermatis (Silva, 2018), Malassezia furfur ( Silva, 2018 ), and Listeria monocytogenes (Ceruso et al, 2020), which are shown in the present article as a result of a 15-year study in antimicrobial-active natural product identification (Suffredini et al, 2002;Suffredini et al, 2004;Suffredini et al, 2006a;Suffredini et al, 2006b;Younes et al, 2007;Castilho et al, 2013;Camargo and Suffredini, 2014;Castilho et al, 2014;da Silva et al, 2014;Costa et al, 2016;Suffredini et al, 2016;Martins et al, 2019a;Martins et al, 2019b;Camargo et al, 2020;Silva et al, 2020).. The present article reports a step-by-step methodology for identifying antimicrobial products in nature that comprises plant collection, the different tests used to analyze the in vitro antimicrobial activity, a test to determine toxicity, and a statistical-based algorithm to classify the extracts according to their potential.…”
Section: Introductionsupporting
confidence: 54%
“…To optimize the costs of the random-chemotaxonomic plant collection strategy, small amounts of plant material are collected in the field, resulting in small amounts of plant extracts, so it is vital to adjust the in vitro assay scales to the use of micrograms of plant extracts A proposed ranking of 111 plant extracts according to their antimicrobial activity efficacy and low toxicity. Suffredini et al 10.3389/frabi.2023.1122400 Frontiers in Antibiotics frontiersin.org (Suffredini et al, 2002;Suffredini et al, 2004;Suffredini et al, 2006a;Suffredini et al, 2006b;Younes et al, 2007;Castilho et al, 2013;Camargo and Suffredini, 2014;Castilho et al, 2014;da Silva et al, 2014;Costa et al, 2016;Suffredini et al, 2016;Martins et al, 2019a;Martins et al, 2019b;Camargo et al, 2020;Silva et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It normally exists as a solid and needs to be stored at low temperatures. Secoxyloganin has anti-inflammatory, vasoconstriction, antiviral, antitumour and antibacterial activities ( Camargo, et al, 2020 ). While identifying the sensitizing components in reducing injection by ultrafiltration and high-performance liquid chromatography.…”
Section: Classification and Overview Of Secondary Metabolitesmentioning
confidence: 99%